2021
DOI: 10.2147/nss.s312037
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Sleep Disturbance During COVID-19 Pandemic: A Systematic Review

Abstract: Coronavirus disease 2019 (COVID-19) pandemic may exert adverse impacts on sleep among populations, which may raise awareness of the burden of sleep disturbance, and the demand of intervention strategies for different populations. We aimed to summarize the current evidence for the impacts of COVID-19 on sleep in patients with COVID-19, healthcare workers (HWs), and the general population. We searched PubMed and Embase for studies on the prevalence of sleep disturbance. Totally, 86 studies were included in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 124 publications
(213 reference statements)
6
72
0
Order By: Relevance
“…Such relational directionality suggests that if someone with relatively low psychological wellbeing proactively engages in resilience-based coping, their sleep quality is better supported. These results are in line with other recent studies on sleep quality during the pandemic, which have shown that change in sleep quality varies based on individual differences [7,61,62]; however, the current study is the first to examine individual differences in situational coping as impacting sleep quality during the pandemic.…”
Section: Main Effect Model and Mediation Modelsupporting
confidence: 92%
“…Such relational directionality suggests that if someone with relatively low psychological wellbeing proactively engages in resilience-based coping, their sleep quality is better supported. These results are in line with other recent studies on sleep quality during the pandemic, which have shown that change in sleep quality varies based on individual differences [7,61,62]; however, the current study is the first to examine individual differences in situational coping as impacting sleep quality during the pandemic.…”
Section: Main Effect Model and Mediation Modelsupporting
confidence: 92%
“… 36 In this case, the first assessment included both the psychological distress of a potential infection and stringent measures of quarantine, limiting their exposure to important environmental sleep promoters. 37 Therefore, the results from our study may have differed from the other longitudinal studies because our first assessment was obtained well before the COVID-19 pandemic began.…”
Section: Discussionmentioning
confidence: 78%
“…For instance, a 2021 meta-analysis reported that worldwide, the prevalence of sleep disturbance has been estimated to be between 18.4 and 84.7% in health care workers and 17.65-81% in the general population. 19 Exposure to the COVID-19 pandemic in the workplace could act as a precipitating factor of a hyperarousal state, which could lead to a higher incidence of sleep disturbance and other sleep disorders when compared with the general population. 3 Sleep dysfunction is often accompanied by psychological distress symptoms among health care workers during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%